The Urgency of Assessing Zakat and Waqf Management Graduates for Achieve Industry Needs (UIN Sunan Kudus, 2022)
One skill of economics students that is still lacking today is the skill in managing zakat and waqf. In fact, the need for zakat and waqf managers for zakat and waqf institutions is immense. the lack of experts in the field of zakat and waqf management, the researcher is interested in conducting research intended for graduates of zakat and waqf management at IAIN Kudus, where this major is still rare in Indonesia and has few enthusiasts, even though the scope of work is very broad and much needed. This research uses a quantitative descriptive research design with a survey approach.The subjects of this research are graduates of the Zakat and Waqf Management Study Program IAIN Kudus from 2017 to 2020, totaling 56 people. Graduates of the Zakat and Waqf management program have found employment, with 35 people or 63% of graduates from 2017 - 2020. This is very good, considering that it is still difficult to get a job at this time. However, although the waiting period also shows good numbers, this is not the case with the suitability of the field of work, which still chooses to work that is not in accordance with their field.